Measurement of Inequity in Health Care with Heterogeneous Response of Use to Need - Ellen van de Poel; Eddy van Doorslaer; Owen O'Donnell (Tinbergen Institute, 2011)
We propose a method of measuring and decomposing inequity in health care utilisation that allows for heterogeneity in the use-need relationship. This makes explicit inequity that derives from unequal treatment response to variation in need, as well as that due to differential effects of non-need determinants. Under plausible conditions concerning heterogeneity in the use-need relationship and the distribution of need, existing methods that impose homogeneity will underestimate pro-rich inequity. This prediction is confirmed for four low-middle income Asian countries.
urn:NBN:nl:ui:15-1765/26864
Keywords: D63; I14; 330; health care; equity; decomposition